Mediterranean diet and diabetic microvascular complications: a systematic review and meta-analysis - Diar Zooravar; Pedram Soltani; Saeed Khezri (BMC Nutrition)
Abstract Background Diabetic microvascular complications, including diabetic retinopathy (DR), diabetic nephropathy (DN), and diabetic peripheral neuropathy (DPN), contribute significantly to morbidity and healthcare burdens among individuals with diabetes. The Mediterranean diet (MD) has been associated with improved metabolic health, but its role in mitigating microvascular complications remains unclear. This systematic review and meta-analysis aimed to assess the impact of MD adherence on the risk and progression of these complications. Methods A comprehensive search of PubMed, Web of Science, Embase, and Scopus was conducted through February 12, 2025 to identify studies evaluating MD adherence and diabetic microvascular complications. Meta-analysis was performed where possible, with effect sizes reported as odds ratios (ORs) or hazard ratios (HRs) with 95% confidence intervals (CIs). Results Fourteen studies, encompassing 138 to 71,392 participants, were included. Meta-analysis indicated a significant reduction in DR risk among individuals adhering to the MD (HR: 0.69, 95% CI: 0.49–0.97, p = 0.03; OR: 0.32, 95% CI: 0.12–0.82, p = 0.02). A lower likelihood of DN development was observed (HR: 0.85, 95% CI: 0.73–0.99, p = 0.04; OR: 0.49, 95% CI: 0.25–0.96, p = 0.04). However, results for diabetic neuropathy were inconclusive due to study heterogeneity. Sensitivity analyses revealed notable heterogeneity and publication bias was detected in some analyses. Conclusion Adherence to the Mediterranean diet is associated with a reduced risk of diabetic nephropathy and retinopathy, supporting its potential as a dietary intervention for diabetes management. However, the evidence for neuropathy remains inconclusive. Future well-controlled randomized trials are needed to strengthen causal inferences and refine clinical recommendations for MD-based interventions in diabetic microvascular complications.